2002
DOI: 10.1002/ps.589
|View full text |Cite
|
Sign up to set email alerts
|

Pirimiphos‐methyl and benalaxyl losses in surface runoff from plots cultivated with potatoes

Abstract: Losses of pirimiphos-methyl and benalaxyl in runoff water from clay soil plots cultivated with potatoes and of differing soil surface slopes were determined over approximately 120 days (1 October 1999-28 January 2000). The plot slopes were 0, 1, 2.5 and 5%, and soil erosion increased with the slope from 610 to 1760kgha(-1). The runoff of surface water was between 3.1 and 16.6% of the rainfall. Surface runoff was highest for the fifth and seventh runoff events due to rainfall, 51 days and 72 days after the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In addition to application patterns and geographical and meteorological conditions, the physicochemical properties of an insecticide (such as its hydrophobicity) are crucial components of its potential to enter a surface water via runoff (36,37). Empirical studies (38,39) suggest that lower runoff losses to surface waters occur for strongly sorbed compounds. This potential provides opportunities for the more efficient use of insecticides based on modeling of their runoff potential.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to application patterns and geographical and meteorological conditions, the physicochemical properties of an insecticide (such as its hydrophobicity) are crucial components of its potential to enter a surface water via runoff (36,37). Empirical studies (38,39) suggest that lower runoff losses to surface waters occur for strongly sorbed compounds. This potential provides opportunities for the more efficient use of insecticides based on modeling of their runoff potential.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the nonenantioselective dissipation in other soils does not necessarily indicate the absence or reduced importance of biological degradation. Patakioutas et al 10 reported that benalaxyl is slowly degraded by micro-organisms in soil to various acidic metabolites. Thus, the difference of the degradation behavior of benalaxyl among the test soils in the present study may be explained that the different soil types may contain different micro-organisms, which preferentially degrade one enantiomer.…”
Section: Stereoselective Degradation In Soilsmentioning
confidence: 99%
“…8 The biodegradation and metabolism of racemic benalaxyl in water, soils, and different plants has been studied extensively and results have demonstrated that the degradation of this chemical in soil is a microbiologically mediated process. [10][11][12][13] This biological process potentially exposes chiral compounds to stereoselective degradation, and similarly, it can be expected that the behavior and the reaction of these compounds with chiral structures (protein such as metabolizing enzymes) of biological systems (plants) are stereospecific. 3 As far as we know, enantioselective degradation of benalaxyl in the environmental matrix has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorptiondesorption studies recovered 83-97% of the pesticide, the persistence studies showed a half-life of 11.5-12.9 days and a persistence beyond 90 days, and the leaching studies recovered 0.02-0.04% from the leachate. Patakioutas et al (2002) reported on the losses of pirimiphos-methyl and benalaxyl in runoff water from clay soil cultivated potato plots of varying soil surface slopes. The surface slope and sorption capacities for the two compounds were the main parameters influencing the transport of these pesticides.…”
Section: Fate and Transportmentioning
confidence: 99%